Endovascular coiling procedure for saccular multilobulated anterior communicating artery aneurysm associated with contralateral A1 segment aplasia - Bilzardy Ferry Zulkifli; Achmad Adam; Christian Beta Kurniawan; Yustinus Robby Budiman Gondowardojo (Neurologico Spinale Medico Chirurgico, 2022)
The anterior communicating artery complex anatomy is very important in treating anterior cerebral circulation aneurysms surgically. About a quarter of all intracranial aneurysms are anterior communicating artery (AcomA) aneurysms. Aneurysm formation may be influenced by anatomic risk factors, with a co-occurring incidence of anterior cerebral artery trunks (A1) asymmetry. Patients with AcomA aneurysm are often presented with anterior cerebral artery A1 segment aplasia/hypoplasia. In this study, we will report a case of A1 hypoplasia in a 42-year-old female with a history of headache 3 days prior to admission which worsened overtime. Traditionally, coiling of A1 hypoplasia was not needed, however due to the neurological deficit, coiling was performed. This case report addresses the comparison between patient’s pre-operative and post-operative results from angiography and coiling.